2002
DOI: 10.1152/ajpendo.00414.2001
|View full text |Cite
|
Sign up to set email alerts
|

Contrasting effects of fish oil and safflower oil on hepatic peroxisomal and tissue lipid content

Abstract: To examine the mechanism by which fish oil protects against fat-induced insulin resistance, we studied the effects of control, fish oil, and safflower oil diets on peroxisomal content, fatty acyl-CoA, diacylglycerol, and ceramide content in rat liver and muscle. We found that, in contrast to control and safflower oil-fed rats, fish oil feeding induced a 150% increase in the abundance of peroxisomal acyl-CoA oxidase and 3-ketoacyl-CoA thiolase in liver but lacked similar effects in muscle. This was paralleled b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
102
0
2

Year Published

2003
2003
2016
2016

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 137 publications
(114 citation statements)
references
References 24 publications
10
102
0
2
Order By: Relevance
“…Long-chain fatty acyl-CoAs were extracted from the muscle sample by solid-phase extraction, and 17-carbon CoA was added as an internal standard, as previously described (2,27). A tandem mass spectrometer API 3000 (Perkin-Elmer Sciex) interfaced with a TurboIonspray ionization source was used for MS-MS analysis (27). Fatty acyl-CoAs were ionized in a negative electrospray mode, and the transition pairs [M-2 H] 2Ϫ /[M-H-80] Ϫ were monitored in multiple reaction monitoring mode.…”
Section: Fatty Acyl-coa Analysesmentioning
confidence: 99%
See 1 more Smart Citation
“…Long-chain fatty acyl-CoAs were extracted from the muscle sample by solid-phase extraction, and 17-carbon CoA was added as an internal standard, as previously described (2,27). A tandem mass spectrometer API 3000 (Perkin-Elmer Sciex) interfaced with a TurboIonspray ionization source was used for MS-MS analysis (27). Fatty acyl-CoAs were ionized in a negative electrospray mode, and the transition pairs [M-2 H] 2Ϫ /[M-H-80] Ϫ were monitored in multiple reaction monitoring mode.…”
Section: Fatty Acyl-coa Analysesmentioning
confidence: 99%
“…Fatty acyl-CoAs were ionized in a negative electrospray mode, and the transition pairs [M-2 H] 2Ϫ /[M-H-80] Ϫ were monitored in multiple reaction monitoring mode. Doubly charged ions and corresponding product ions (precursor minus phosphate group) were chosen as a transition pair for multiple-reactions monitoring for quantitation (27). Total long-chain fatty acyl-CoA content was calculated as the sum of the long-chain fatty acyl-CoA species measured.…”
Section: Fatty Acyl-coa Analysesmentioning
confidence: 99%
“…The following mechanisms are likely to be implicated: (a) the decrease in muscle triglyceride content. Indeed, it has been shown that insulin sensitivity is related to muscle triglycerides in rats fed a high fat diet and that muscle triglyceride content is decreased by fish oil [34,35]; (b) the decrease in LCFACoA as demonstrated by Neschen et al [36]; (c) the decrease in visceral fat mass [37]; (d) the increase in unsaturation of membrane phospholipids. A strong positive relationship has been shown between the insulin sensitivity of rat muscles and the degree of unsaturation of muscle membrane phospholipids [32].…”
Section: Animal Models Of Insulin Resistancementioning
confidence: 99%
“…In rats fed a high fat diet, substitution for fish oil in the diet reduces liver triglyceride content [35,36]. n-3 PUFA exert their effects by coordinately suppressing lipogenesis and upregulating fatty acid oxidation.…”
Section: Patients With Nonalcoholic Steatohepatitismentioning
confidence: 99%
“…These data raise the question of whether acquired obesity indeed regulates liver fat content. Alternative regulators would be genetic factors and acquired factors other than obesity, such as dietary fat content and composition (24,44).…”
mentioning
confidence: 99%